Philosophical foundations of the nature of law - Waluchow, Wilfrid J.; Sciaraffa, Stefan (Philosophical foundations of law., 2013)
In recent years we have witnessed major developments in philosophical inquiry concerning the nature of law and, with the continuing development of international and transnational legal institutions, in the phenomenon of law itself. This volume gathers leading writers in the field to take stock of current debates on the nature of law and the aims and methods of legal philosophy. The volume covers four broad themes. The essays within the first theme address and develop the traditional debates between legal positivism, natural law theory, and Dworkinian interpretivism. Papers within the second the.